An Innovative Biomaterial: 45S5 Bioactive Glass Functionalized with PTH 1–34 In Vivo Bone Repair - de Araújo, Juliani Caroline Ribeiro [UNESP]; Silva, Leonardo Alvares Sobral [UNESP]; de Oliveira, Elisa Freire Sant’Anna [UNESP]; Vieira, Marília Nanni [UNESP]; Filho, Paulo Noronha Lisboa [UNESP]; Campos, Tiago Moreira Bastos; Okamoto, Roberta [UNESP]; de Vasconcellos, Luana Marotta Reis [UNESP] (Springer Nature, 2025)
Developing functional biomaterials with optimized properties is a major challenge in tissue engineering. Materials such as bioactive glasses have been widely studied due to their potential for bone regeneration. In the present study, we aimed to develop 45S5 bioactive glass functionalized with 10% PTH 1–34 and evaluate the effects of the biomaterial on bone regeneration and the healing of critical bone defects in female rats. The preparation of the biomaterial involved the production of 45S5 bioactive glass using the sol–gel technique, followed by melting and quenching. To this end, thirty female Wistar rats were randomly assigned to two groups: one with 5-mm critical bone defects in the calvaria and another with 3-mm defects in the tibiae. The defects were filled with either bioactive glass (BG) or bioactive glass functionalized with 10% teriparatide (BGTer). The animals were euthanized at 2- and 6-weeks post-operation, and their defects were analyzed using histological, histomorphometry, immunohistochemical, and biomechanical methods (via a three-point bending test). Data were statistically assessed using ANOVA and Tukey’s post hoc test, with a significance level of 5%. The results showed that PTH 1–34, associated with the bioactive glass, was successfully incorporated and had a positive effect on bone repair in the studied model. We concluded that the biomaterial minimized the potential side effects and complications associated with systemic administration by transforming PTH 1–34 into a localized delivery system, representing a significant innovation of medical bioengineering.
Keywords: Biocompatible Materials; Bone Development; Bone Regeneration; Teripatide; Tissue Engineering